The Role of Immunomodulatory Receptors in the Pathogenesis of HIV Infection: A Therapeutic Opportunity for HIV Cure? - Chen, Hui; Moussa, Maha; Catalfamo, Marta (Frontiers in Immunology, 2020)
Immune activation is the hallmark of HIV infection and plays a role in the pathogenesis of the disease. In the context of suppressed HIV RNA replication by combination antiretroviral therapy (cART), there remains immune activation which is associated to the HIV reservoirs. Persistent virus contributes to a sustained inflammatory environment promoting accumulation of “activated/ exhausted” T cells with diminished effector function. These T cells show increased expression of immunomodulatory receptors including Programmed cell death protein (PD1), Cytotoxic T-Lymphocyte Associated Protein 4 (CTLA4), Lymphocyte activation gene 3 (LAG3), T cell immunoglobulin and ITIM domain (TIGIT), T-cell immunoglobulin and mucin-domain containing 3 (TIM3) among others. More importantly, recent reports had demonstrated that, HIV infected T cells express checkpoint receptors, contributing to their survival and promoting maintenance of the viral reservoir. Therapeutic strategies are focused on viral reservoir elimination and/or those to achieve sustained cART-free virologic remission. In this review, we will discuss the immunological basis and the latest advances of the use of checkpoint inhibitors to treat HIV infection.